Assessment of Chlorophyll Content Based on Image Color Analysis, Comparison with SPAD-502 - Hao Hu; He-qin Liu; Hao Zhang; Jing-huan Zhu; Xu-guo Yao; Xiao-bin Zhang; Ke-feng Zheng (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Leaf color has been commonly used as an index for crop stress status diagnosis. We have developed a low-cost and non-destructive method that is easy to use to assess the health status of plants, based on the estimation of chlorophyll content of leaves using a portable digital camera. Relationships between chlorophyll content and leaf image color indices in the RGB and Lab* space with the comparison of SPAD are examined. The RGB color indices of R, G and R+G+B, R-B, R+B, R+G and The Lab* space parameters L*, a* and b* had the significant relationship with chlorophyll content. Although the determination coefficient and prediction confidence intervals of color indices regression were not good than SPAD, the leave imaged tools had the profit of easy operation, found everywhere and no much money cost. The indices from leaf color image analysis maybe used to estimate chlorophyll content.